Humanistic-Digital Curriculum: The Answer to the Challenge of Employability Skills for Vocational School Graduates in the Era of Society 5.0 - Nusaibah, Shifa; Wibowo, Hanafi Reza; Azizah, Sabila Nur; Romandhoni, Fitria; Kamal, Jamaluddin; Naratosa, Savira Putri; Zain, Jihan Zulfa; Farchan, Achmad (Universitas Negeri Semarang, 2025)
The Society 5.0 era demands that the education sector produce human resources who are not only digitally literate but also possess a humanistic character and the ability to adapt to social changes and industrial needs. Vocational high school (SMK) graduates in Indonesia still face a competency gap with the demands of the world of work, especially in terms of employability skills such as creativity, communication, collaboration, and problem solving. This study aims to examine the potential of humanistic-digital curriculum innovation as an alternative approach to improving the employability skills of SMK graduates in the Society 5.0 era. The method used is a Systematic Literature Review (SLR) by examining scientific articles indexed by SINTA, Garuda, and Google Scholar in the 2020–2025 period. The results of the study show that the humanistic-digital curriculum has strategic potential in improving employability skills through the strengthening of soft skills based on humanistic learning, the integration of literacy and digital competencies relevant to industry needs, and the application of collaborative, reflective, and digital project-based learning. Although its implementation still faces structural obstacles, the humanistic-digital curriculum can be an innovative alternative in preparing vocational school graduates who are more adaptive, collaborative, and competitive in facing the dynamics of the world of work in the Society 5.0 era.